TANGGUNG JAWAB NEGARA DALAM PEMENUHAN HAK ATAS KESEMPATAN BERUSAHA BAGI FAKIR MISKIN DI MASA PANDEMI CORONA VIRUS DISEASE-19 - Glien Excell Julio Marshanda; Zulfikar Jayakusuma; Junaidi Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The state has an obligation to prosper all its citizens from poverty as mandated in thePreamble of the 1945 Constitution of the Republic of Indonesia, including caring for thepoor. As stated in Article 34 paragraph (1) of the 1945 Constitution which states that